2004
DOI: 10.1177/021849230401200307
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement with the Medtronic Freestyle Stentless Bioprosthesis

Abstract: During a five-year period from 1996 to 2000, the Medtronic Freestyle stentless bioprosthesis was implanted in 310 patients of advanced age. Age at operation ranged from 60 to 90 years (mean, 76 +/- 4 years). 191 patients were female and 119 male. All implants were done by the modified subcoronary method using our own modification which enabled an improved adaptation of the porcine aortic root to the human anatomy. Two sinuses were scalloped and the third left intact. Additional coronary bypass grafts were nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…3 We have further modified and standardized this procedure. 4 The aneurysmally dilated aortic root is more conical than cylindrical, and our method converts it back to a cylinder to avoid dead space between the aorta and the porcine valve. Arterial cannulation was carried out on the aortic arch in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…3 We have further modified and standardized this procedure. 4 The aneurysmally dilated aortic root is more conical than cylindrical, and our method converts it back to a cylinder to avoid dead space between the aorta and the porcine valve. Arterial cannulation was carried out on the aortic arch in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Over 21,000 of these valves have been implanted during the last 10 years. The vast majority of these implants have been done using the modified subcoronary method which we have already reported and described in detail [3].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Over 21,000 of these valves have been implanted during the last 10 years. The vast majority of these implants have been done using the modified subcoronary method which we have already reported and described in detail [3].High arterial cannulation on the aortic arch enables clamping of the aorta just below the origin of the brachiocephalic trunk. Cardioplegia is usually given retrograde through a catheter in the coronary sinus.…”
mentioning
confidence: 99%
“…Despite small population studies, all patients in the above reports were free from recurrent endocarditis. Recently, John et al 17 reported only 1 valve-related death due to infection of the Freestyle valve among 310 patients of advanced age. The excellent postoperative hemodynamic performance of the Freestyle valve has been demonstrated, 18 -23 and further experimental or clinical prospective evaluations should be required to elucidate whether the Freestyle bioprosthesis can be used as an alternative to homografts in the treatment of severe endocarditis and for the prevention of recurrent endocarditis.…”
Section: Commentsmentioning
confidence: 99%